Prospects for the United States’ post-COVID-19 policies : strengthening the G20 leaders process (2020)
The COVID-19 pandemic has confronted the international system with its second major challenge of the past fifteen years. The first challenge—the global financial crisis (GFC) of 2007–9—led to the creation of the Group of 20 Leaders Summit process.1 The response of this new grouping to its first challenge appeared to be coherent, credible, and effective. The G20’s contribution to the response to the current challenge—the coronavirus pandemic—has seemed much less so. Nonetheless, individual G20 countries’ economic policy response to the pandemic has been rapid and massive, though not coordinated with other G20 partners. What is the future of the G20 in a post-Covid-19 world? Ultimately, the US authorities, who played a critical role in the G20’s formation, will have to decide whether to maintain support for the G20 leaders’ self-definition as “the premier forum for international economic cooperation.”2 A critical consideration will be whether the emergence of China as a global economic power should and will influence US (and others’) views regarding the future role for the exiting international institutions.